Attentive Options Traders: Textual Changes to 10-Ks and Option Volatility Smirk - Cheng, Hua; Liu, Steve; Qiao, Zheng; Wang, Z. Jay (Journal of Financial and Quantitative Analysis, 2026)
Abstract In contrast to the “lazy prices” phenomenon in the stock market, more 10-K textual changes lead to larger increases in volatility smirks—consistent with options traders buying more out-of-the-money put options based on negative information disclosed in textual changes. Moreover, the lazy-prices effect is mainly driven by stocks with tradable options, suggesting that limits to arbitrage lead to a delayed response of stock prices. Finally, the return predictability of textual changes is stronger for stocks with larger option volatility smirk changes. Sophisticated options traders, therefore, demonstrate superior skills at extracting relevant information from public filings.